A plasma strategy for high-quality Si/C composite anode: From tailoring the current collector to preparing the active materials. (1st July 2020) - Zhang, Z.D.; Zhou, H.P.; Feng, T.T.; Zhao, R.; Wang, Y.; He, M.; Xu, Z.Q.; Liao, J.X.; Xue, W.D.; Wu, M.Q.
Abstract: Herein we propose a novel plasma-based route to synergistically modulate the microstructures of the current collectors of nickel foam and subsequently the Si/C composite active coatings, restraining the huge volume expansion of silicon anode materials during lithiation/delithiation in Lithium ion batteries. The nickel foam surface is tailored to form the temperature-dependent nanostructures by the Ar/H2 -plasma. And a 3D Si/C nano-composite structure is constructed in combination of silicon via magnetron sputtering and carbon through the inductively coupled plasma vapor deposition (ICP-CVD). The plasma-activated nickel foam surface leads to the crystallization of the sputtered silicon, and the significantly increased surface area results in the increases of loading rate of Si/C composites (e.g., 75% @room temperature). The electrochemical performance, e.g., the specific capacity, cycle stability and the initial Coulombic efficiency of the composite anode is drastically improved by the plasma processing. The cauliflower-like Si/C composites on the Ar/H2 -plasma modified nickel foam at 300 °C exhibits a high capacity of 1941.2 mA h g −1 at 0.1 A g −1 after 100 cycles, and 976 mA h g −1 at 1.6 A g −1 after 500 cycles, increasing by 3–7 times in terms of the current density when compared with the case without the plasma processing. Highlights: Abundant nanostructure of nickel foam tailored by Ar/H2 plasma. The plasma-activated nickel foam surface leads to the crystallization of the sputtered silicon. The significantly increased surface area of nickel foam results in the increases of loading rate (e.g., 45% @300 °C). The plasma modified nickel foam drastically boosted the electrochemical performance of the 3D Si/C nano-composite anode.